2019
DOI: 10.1136/bmj.l2301
|View full text |Cite
|
Sign up to set email alerts
|

New preprint server for medical research

Abstract: Announcing the launch of medRxiv for faster access to better evidence

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 8 publications
(9 reference statements)
1
51
0
6
Order By: Relevance
“…This approach of sharing research as quickly as possible is very reasonable, especially in the case of such public health emergency. Previous studies have shown that preprints can accelerate progress in handling outbreaks of infectious disease [132,133].…”
Section: Date (2020)mentioning
confidence: 99%
“…This approach of sharing research as quickly as possible is very reasonable, especially in the case of such public health emergency. Previous studies have shown that preprints can accelerate progress in handling outbreaks of infectious disease [132,133].…”
Section: Date (2020)mentioning
confidence: 99%
“…Such papers had a specific screening process involving a group of medically qualified bioRxiv Clinical Affiliates. In 2019, the success of this pilot resulted in the launch of a dedicated preprint server for clinical research, medRxiv (Bloom, 2019;Rawlinson, 2019), and the bioRxiv Epidemiology and Clinical Trials subject categories stopped accepting new papers.…”
Section: Preprint Screeningmentioning
confidence: 99%
“…Researchers in physics, computational science, mathematics, and various other disciplines routinely post manuscripts on arXiv prior to peer review and by mid-2019 the site had posted more than 1.5M papers. Several attempts were made to replicate the approach in the biological sciences (Marshall, 1999;Nature Publishing Group, 2012;Rawlinson, 2019). These were unsuccessful in part because of opposition from traditional publishers but also because there was little interest among biologists.…”
Section: Introductionmentioning
confidence: 99%
“…Lack of a peer-review process in preprints may be an important implication, due to the fact that the basic screening process employed by preprint servers may not be enough to avoid the dissemination of awed information (18). For example, a preprint that was posted on bioRxiv suggested signi cant molecular similarities between SARS-CoV-2 and HIV (19).…”
Section: Discussionmentioning
confidence: 99%